The Konsep Fikih Otoritatif dalam Pendekatan Hermeneutika Khaled Abou El Fadl - Fajrul Falah (Syntax Literate, 2022)
This article discusses about Abou El Fadls hermeneutic thought which responses to the spreading of otoritarianism fatwa in America and Kingdom of Saudi Arabia. This research is a normative juridical research using a conceptual approach from the thoughts of Khaled Abou El Fadl who criticizes fatwas that discredit women's gender rights and biases under the pretext of saying that this is God's will. The results of this study illustrate that the Hermeneutics offered by Abou El Fadl consists of three components, the author, the text and the reader. In this case, the author, Abou El Fadl focuses more on the sunnah and does not criticize the Qur'an because it is included in the realm of faith. This in the text he wants the text to always be open and read with a study of history without avoiding the normative values ​​in it. Meanwhile, in terms of the reader, the leader of the reader must master the five requirements that he has conceptualized so that he is not arbitrary in his storage.